Differences in Water Consumption Choices in Ghadames City: Perceptions of Environmental and Health Risks - Awatif Ahmed Almaqrahi; Fatma Sila Abolgasem; Ehabeddin ELftisi; Hafsa A. Alemam (African Journal of Advanced Pure and Applied Sciences, 2025)
Safe and reliable drinking water is a fundamental public health concern, particularly in arid regions where water sources may be limited or vulnerable to contamination. The results revealed a clear dominance of bottled water consumption (53%), followed by domestic desalinated water (51%), indicating a decline in trust toward traditional water sources. The preference for bottled water was primarily driven by health and contamination concerns (56%), better taste (48%), and availability (36%), while the low reliance on wells and public network water was linked to uncertainty about chemical composition and supply safety. Information about water quality was mostly obtained through the internet (34%) and bottle labels (38%). Participants also expressed specific health related fears, including the absence of essential minerals in bottled water and the potential hazards of plastic containers, whereas concerns about tap or well water centered on mineral content, chlorine levels, and supply quality. Overall, the findings underscore a growing public preference for bottled and filtered water due to perceived safety and quality advantages, coupled with a declining confidence in local water infrastructure.